Life Course Impact of Glucocorticoids During Pregnancy on Muscle Development and Function - Liu, Yang; Ding, Qiyue; Guo, Wei (Frontiers in Animal Science, 2021)
Maternal stress, such as maternal obesity, can induce severe gestational disease and hormonal disorder. These antenatal effects may disrupt fetal organ maturation, thus causing endangered early or future health in offspring. During fetal development, glucocorticoids are essential for the maturation of organ systems. However, exposure of excessive glucocorticoids at embryonic and fetal developmental stages can cause diseases such as cardiovascular disease and muscle atrophy in adulthood. In clinical applications, glucocorticoids are commonly utilized to pregnant women with the risk of preterm delivery to reduce mortality of the newborns. The effects of glucocorticoids on human health are well recognized and extensively studied. It’s impact on farm animal growth and development, particularly on prenatal muscle development and postnatal growth, does not attract much attention until the last decade. Here, we provided a short review of the recent progress relating to the effect of glucocorticoids on prenatal skeletal muscle development and postnatal muscle growth as well as heart muscle development and cardiovascular disease later in life.